Creolising Textiles Some new light on textile production and consumption in Roman Age Free Germania - Kaczmarek, Zofia (My University, 2017)
Creolisation is a concept of multicultural adjustment through which new societies are born, which can be successfully applied to the romanisation of the Roman provinces. This paper shows that it is applicable to the Roman period textiles found in Free Germania, especially those found in the territory of modern Poland. Creolisation assumes that the ‘barbarians’ were not passive in adopting Roman influence, but blended it with their own cultures sometimes for aesthetic but often for pragmatic reasons. In Germania Libera, new textiles were produced which were an amalgamation of not only Roman and local traditions but also of those of the neighbouring barbarian cultures. A common simplification assumes that the Germanic people were only interested in accepting Roman influence. However, this assumption is questionable. Archaeological material shows that the Germanic tribes stayed in contact with each other. This means that they also influenced each other’s fashion and weaving technology. That is why, when Roman influences reached Free Germania, they met an established mixture of different Germanic traditions. This suggests that new patterns of spin direction and different qualities of textiles, which can be observed in textiles of the Roman period, were not influenced by the Romans alone. The concept of creolisation helps to explain how complicated the contacts were between the Romans and Germans, and how difficult it is to determine Roman influence in textile production and consumption.
Keywords: Romanizacja; Kreolizacja; Importy rzymskie; Tkaniny archeologiczne